(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The idiomatic expressions related to luck and misfortune in any language serve as a mirror of cultural memory, collective psychology, and national identity. This paper explores the idioms representing these two universal yet culturally diverse concepts in Uzbek and English languages. Using a comparative and metaphorical-semantic approach, the study reveals how each language encodes luck and misfortune through culturally resonant metaphors, traditional symbols, and socially rooted expressions. While some idioms share universal conceptual metaphors, such as celestial imagery (e.g., stars, fate), others reflect unique cultural values and taboos, deeply tied to folk beliefs, religious ideas, and historical experience. The paper also discusses the pragmatic function of these idioms in real-life communication, their emotional connotation, and their significance in translation studies. Finally, it argues that understanding such phraseological units can promote more effective intercultural dialogue and foster linguistic sensitivity in both academic and applied contexts.